2021
DOI: 10.1016/j.crphar.2021.100053
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cotranslational translocation by apratoxin S4: Effects on oncogenic receptor tyrosine kinases and the fate of transmembrane proteins produced in the cytoplasm

Abstract: Receptor tyrosine kinases (RTKs) have become major targets for anticancer therapy. However, resistance and signaling pathway redundancy has been problematic. The marine-derived apratoxins act complementary to direct kinase inhibitors by downregulating the levels of multiple of these receptors and additionally prevent the secretion of growth factors that act on these receptors by targeting Sec61α, therefore interfering with cotranslational translocation. We have profiled the synthetic, natural product-inspired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A different type of Sec61 inhibitor, ipomoeassin F, was recently shown to inhibit the in vitro biogenesis of both spike protein and the SARS-CoV receptor ACE2; however, this observation remains to be confirmed in cell culture models . Consistent with the known effects of Apra S4 on host membrane proteins, Apra S4 additionally downregulates ACE2, although not completely. Further studies are required to determine if this indirect effect would additionally interfere with virus entry upon longer exposure to Apra S4 (Figure ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A different type of Sec61 inhibitor, ipomoeassin F, was recently shown to inhibit the in vitro biogenesis of both spike protein and the SARS-CoV receptor ACE2; however, this observation remains to be confirmed in cell culture models . Consistent with the known effects of Apra S4 on host membrane proteins, Apra S4 additionally downregulates ACE2, although not completely. Further studies are required to determine if this indirect effect would additionally interfere with virus entry upon longer exposure to Apra S4 (Figure ).…”
Section: Discussionmentioning
confidence: 95%
“…Apratoxin S4 (Apra S4) is a synthetic hybrid analogue of apratoxins A/E, which prevents protein translocation by directly targeting Sec61α, the central subunit of the protein translocation channel on the endoplasmic reticulum (ER) membrane. , Among known Sec61 inhibitors, apratoxins possess unique resistant profiles in cancer cells, indicating a unique mode of target interaction. , It prevents protein ER translocation at an earlier stage than cotransin and appears to impact ER import of Sec61 substrate proteins in a substrate-nonselective fashion based on biochemical data . However, the substrate selectivity for host proteins is tunable and highly context-dependent, as we recently reported . Since viral glycoproteins are dependent on Sec61-mediated secretion, we observed blockage of viral proteostasis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Moreover, it is unclear why some secretory and Type-I membrane proteins are more sensitive to CbA (1), or AprA, than closely related Sec61 clients with similar primary sequence homology. 37,43,44 Given the structural complexity and physiochemical properties of lariat depsipetide scaffolds, 45 the present study aimed to assess the potential impact of stereoselectivity on the action of 1. Several research groups have previously shown that single alterations in the stereochemistry of chiral centers in the macrocycle, or tail, of 1, results in significant decreases in cytotoxic potency relative to the authentic natural product.…”
mentioning
confidence: 99%
“…Although all Sec61 inhibitors are predicted to bind and compete for a common region within the Sec61α subunit, extensive resistance mapping in cells and advanced structural models have confirmed that these ligands form nonidentical interactions with Sec61. ,,,,,, Point mutations in Sec61α conferring strong resistance to the broad-spectrum cyanobacterial Sec61 inhibitor apratoxin A (AprA), confer only mild resistance to 1 , which suggests that the two molecules bind distinct interfaces or possibly different conformational states of the native channel . Moreover, it is unclear why some secretory and Type-I membrane proteins are more sensitive to CbA ( 1 ), or AprA, than closely related Sec61 clients with similar primary sequence homology. ,, Given the structural complexity and physiochemical properties of lariat depsipetide scaffolds, the present study aimed to assess the potential impact of stereoselectivity on the action of 1 . Several research groups have previously shown that single alterations in the stereochemistry of chiral centers in the macrocycle, or tail, of 1 , results in significant decreases in cytotoxic potency relative to the authentic natural product. ,,, We compared the pharmacological properties of 1 , and two major diastereoisomers, against a panel of patient-derived glioblastoma (GBM) stem-like cells (GSCs) with clinically relevant features of GBM including the amplification of known Sec61 substrates such as EGFR and PDGFR (Figure S1).…”
mentioning
confidence: 99%